Long-Term Clinical Outcome in Elderly Patients Undergoing Mitral Valve Repair - Götte, Julia; Zittermann, Armin; Hakim-Meibodi, Kavous; Hata, Masatoshi; Schramm, Rene; Bleiziffer, Sabine; Parsa, Mohammed Amin; Gummert, Jan; Renner, Andre (The Thoracic and Cardiovascular Surgeon, 2020)
Background Long-term data on patients over 75 years undergoing mitral valve (MV) repair are scarce. At our high-volume institution, we, therefore, aimed to evaluate mortality, stroke risk, and reoperation rates in these patients.Methods We investigated clinical outcomes in 372 patients undergoing MV repair with (n = 115) or without (n = 257) tricuspid valve repair. The primary endpoint was the probability of survival up to a maximum follow-up of 9 years. Secondary clinical endpoints were stroke and reoperation of the MV during follow-up. Univariate and multivariable Cox regression analysis was performed to assess independent predictors of mortality. Mortality was also compared with the age- and sex-adjusted general population.Results During a median follow-up period of 37 months (range: 0.1–108 months), 90 patients died. The following parameters were independently associated with mortality: double valve repair (hazard ratio, confidence interval [HR, 95% CI]: 2.15, 1.37–3.36), advanced age (HR: 1.07, CI: 1.01–1.14 per year), diabetes (HR: 1.97, CI: 1.13–3.43), preoperative New York Heart Association (NYHA) functional class (HR: 1.41, CI: 1.01–1.97 per class), and operative creatininemax levels (HR: 1.32, CI: 1.13–1.55 per mg/dL). The risk of stroke in the isolated MV and double valve repair groups at postoperative year 5 was 5.0 and 4.1%, respectively (p = 0.65). The corresponding values for the risk of reoperation were 4.0 and 7.0%, respectively (p = 0.36). Nine-year survival was comparable with the general population (53.2 vs. 53.1%).Conclusion Various independent risk factors for mortality in elderly MV repair patients could be identified, but overall survival rates were similar to those of the general population. Consequently, our data indicates that repairing the MV in elderly patients represents a suitable and safe surgical approach.
Keywords: mitral valve; tricuspid valve; valve repair; mortality; age